Discoveries and opinions of Galileo - Galilei, Galileo 1564-1642 (Garden City, New York Doubleday, 1957)
Contains the English translations of four writings by Galileo that state his theories on major aspects of science and experimentation.
The starry messenger -- Letters on sunspots -- Letter to the Grand Duchess Christina -- Excerpts from the Assayer.